Contrast Response Functions with Wide-View Stimuli in the Human Visual Cortex. (July 2014) - Yan, Tianyi; Wang, Bin; Geng, Yansong; Yan, Yaqi; Mu, Nan; Wu, Jinglong; Guo, Qiyong; Tang, Xiaoying; Zeng, Yanjun; Peng, Yuhua
In this manuscript, using a novel wide-view visual presentation system that we developed for vision research and functional magnetic resonance imaging (fMRI), we studied contrast response functions in regions of the brain that are central and peripheral to the entire set of visual areas (V1, V2, V3, V3A, MT+), regions that have not been all investigated in previous vision research. Under the stimulus conditions which were 0–20 deg, 20–40 deg, and 40–60 deg eccentricity black-and-white checkerboard patterns, we measured the blood oxygenation level-dependent fMRI contrast response at five contrast levels (6, 12, 24, 48, and 96%) in the visual areas. On the basis of these data, the central and pericentral visual areas had low-contrast gain, whereas the peripheral visual areas had high-contrast gain. In addition, our results showed that the signals fundamentally shift during visual processing through posterior visual cortical areas (V1, V2, and V3) to superior visual cortical areas (V3A and MT+).